Impact of Incentive System on Employees’ Motivation in Small and Medium Enterprises (SMEs): A Case Study in Wholesale Trade Sub-Sector Company - Hao, Ng Mei (Universiti Malaysia Sarawak (UNIMAS), 2021)
Small and Medium Enterprises (SMEs) constantly have many obstacles in designing incentive systems as compared to large organizations or other Multinational Corporate (MNC). Particularly during this pandemic, feasible and attainable incentive systems which can motivate employees rather than demotivate them in a retrenchment mode must be devised. This research aims to study the impact of the incentive system on employee’s motivation in Redquay Sdn Bhd before and during this pandemic. Specifically, it investigates the characteristics of the previous and the current incentive system that Redquay’s employees seem as motivating. In this context, incentive system is defined as a system implemented by a company/organization to reward their employee’s performance and dedication, while retaining their motivation. This research employs the qualitative methodology using semi-structured interviews as the main data collection tool. The study revealed that the incentive system with characteristics of specific, clear, attractive, fair, and attainable is the system that employees look forward to and seem as motivating. This suggests that the company should revisit and revise back the incentives policies, as well as clearly clarify incentives implemented in the company with details about terms and conditions (T&C) of the incentives in writing. As a result, in motivating employees, adopt any or all of the employees mentioned incentive system characteristics. This will surely have an impact on their attitudes toward work and enhance productivity.